In vitro combinatory antimicrobial effect of crude bacteriocins from Pediococcus pentosaceus strains and selected antibiotics against Pseudomonas aeruginosa ATCC 10145 - Suffian, Suffi Nurul Husna (2020)
Pseudomonas aeruginosa presents a major challenge for treatment in nosocomial infections due to the ability of P. aeruginosa to rapidly develop resistance to multiple antipseudomonal drugs during treatment. This high resistance has severely limited the therapeutic options for P. aeruginosa infections and caused serious complications such as increase in morbidity and mortality. The increased in multidrug-resistant (MDR) P. aeruginosa strains in recent years gave urgency to the discovery of new strategy to combat MDR P. aeruginosa infections. Hence, this study explores the efficiency of using crude bacteriocins from Pediococcus pentosaceus isolated from local fermented foods and in combination with selected antibiotics to revoke the multi-drug resistance ability of P. aeruginosa ATCC 10145. Forty-two lactic acid bacteria (LAB) were isolated from tempeh, tapai ubi and tapai pulut. Only seven isolates successfully inhibited P. aeruginosa ATCC 10145 with modified bacteriocin activity that ranging from 31.67 to 126.67 AU.cm/ml. Three LAB, namely TU2, TP1 and TE1 with the highest modified bacteriocin activity were identified as Pediococcus pentosaceus via API 50 CHL carbohydrate fermentation test and 16S rDNA sequencing. Crude bacteriocins TU2, TP1 and TE1 demonstrated MIC of 15.63 mg/ml against P. aeruginosa ATCC 10145. Meanwhile, P. aeruginosa ATCC 10145 displayed high sensitivity towards ciprofloxacin at MIC of 0.25 µg/ml, while remained resistant to tetracycline and chloramphenicol at MIC 32 µg/ml. The fractional inhibitory concentration (FIC) checkerboard assay revealed that the combination respective tetracycline and ciprofloxacin with crude bacteriocins resulted in synergistic interaction in inhibiting P. aeruginosa ATCC 10145. While, the combination of crude bacteriocins and chloramphenicol had indifferent effects. Time-kill assay further confirmed the synergistic interaction of combination of crude bacteriocins with tetracycline with bactericidal inhibition detected after 10 h of incubation. However, the combination of crude bacteriocins with chloramphenicol also successfully inhibited P. aeruginosa ATCC 10145 totally after 8 h of incubation. Contradict to the result of FIC assay, the time-kill assay revealed that treatment with ciprofloxacin alone was more effective in killing P. aeruginosa ATCC 10145 within 2 h of incubation than in combination with crude bacteriocins. Untreated P. aeruginosa ATCC 10145 (control) cells were observed to be rod-shaped, smooth and intact cell walls and membrane without any morphological changes at 4 h and formed clumps of cells after 8 h of incubation when examined under scanning electron microscope (SEM). In contrast, treatment of crude bacteriocin TU2 in combination with all antibiotics (chloramphenicol, ciprofloxacin and tetracycline) resulted in similar cell surface morphological changes of P. aeruginosa ATCC 10145 such as formation of pores on the cell membranes at 2 h, cell membranes ruptured and released of the cellular contents at 4 h, and cell lysis occurred, resulting in cell death at 8 h of incubation. However, the combination of crude bacteriocin TU2 with chloramphenicol showed distinct cell surface morphological changes such as cell elongation at 2 h of incubation. Whilst P. aeruginosa ATCC 10145 cells revealed to be shorter and formed chains when treated with crude bacteriocin TU2 in combination with ciprofloxacin. When compared the three combinations of bacteriocin TU2 with all antibiotics, only the combination of crude bacteriocin TU2 with chloramphenicol caused 100% killing of P. aeruginosa cells in the shortest time at 8 h. Hence, the treatment of crude bacteriocin TU2 with chloramphenicol produced the best combination against P. aeruginosa ATCC 10145 in this study. SEM images revealed that the the crude bacteriocins enhanced the effects of antibiotics by forming pores on the target membrane of P. aeruginosa ATCC 10145 which resulted in cell death. Further studies need to be carried out to provide insights into the action mechanisms of the combination of crude bacteriocins and antibiotics against P. aeruginosa prior to future medical and therapeutic applications.